Interventions to support victims of domestic violence: health service responses and a multi-agency model. (1st March 2011) - Barran, D; Feder, G
Abstract : Historically healthcare has lagged other sectors in responding effectively to domestic violence, despite its significant public health impact and the view of survivors that they want support from doctors. As part of the UK Department of Health's taskforce on "Responding to violence against women and children" a domestic violence subgroup made recommendations including: Prevention: Healthcare professionals should work in partnership with other sectors in challenging the acceptability of domestic abuse among young people. Identification and management: Clinical teams need training to ensure they use safe enquiry to identify domestic violence and offer appropriate services to their patients. Key services and successful pathways: Commission intervention programmes for women survivors and their children. Services may include community based provision such as independent domestic violence advisers (IDVAs), and specialist support services for children and young people. Integration of psychological support and treatment for survivors and their children into mainstream primary and secondary healthcare. Improving availability of and access to services: Provide national guidance on commissioning of specialist domestic violence services for women and children that can be accessed from primary care, women's health and emergency health settings. Information sharing: Integrate child protection and domestic violence information sharing, to create a two-way flow of information between these two services. We will conclude with the key quantitative findings of the first multi-site evaluation of IDVAs in the UK, exemplars of an innovative, evidence-based intervention.